STRATEGIES OF THE NATIONAL CLIMATE MANAGEMENT SYSTEM TOWARDS REDUCING CARBON EMISSIONS - Nadia Mahmoud Tawfiq Jebril; Hala R. Mohammed; Shahad Ahmad Mezher; Sarah Hussein Hamzah; Fatin Fahim Ouda Al-janabi (Scholars Digest Publishing, 2024)
Global climate governance has sought to reduce carbon emissions, with an increasing number of countries setting this target for long-term emissions reductions on the way to the mid-21st century. Iraq has also pledged to this goal, which necessitates the establishment of an integrated, systematic national climate management system. Therefore, in this study, available strategies concerning climate administration systems will be addressed. The study shows that although strategies exist between decarbonization and other environmental, social and economic areas, research gaps still exist when promoting climate management towards this goal. For example, issues related to assimilating climate factors into overall economic and social planning, enhancing capability to collect data relevant to climate adaptation, integrating climate mitigation and version actions, as well as linking local climate management and international cooperation, must be reassessed. We need studies that monitor and evaluate the applied strategy. Moreover, the division of strategies and communication system between state and non-state actors is also important. Based on this study, further policy decisions and implementation of long-term climate management strategies towards carbon neutrality are proposed.
Keywords: carbon neutrality, national climate management system, design at the highest level, governance model, climate adaptation.